2019
DOI: 10.1002/pmic.201800271
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Edged Sword: Complement Component 3 in Toxoplasma gondii Infection

Abstract: Sprague Dawley rats and Kunming (KM) mice are artificially infected with type II Toxoplasma gondii strain Prugniaud (Pru) to generate toxoplasmosis, which is a fatal disease mediated by T. gondii invasion of the central nervous system (CNS) by unknown mechanisms. The aim is to explore the mechanism of differential susceptibility of mice and rats to T. gondii infection. Therefore, a strategy of isobaric tags for relative and absolute quantitation (iTRAQ) is established to identify differentially expressed prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 110 publications
(151 reference statements)
2
10
0
Order By: Relevance
“…In addition, C4A has been associated with roles in schizophrenia (Liesmaa et al, 2018;Melbourne et al, 2018;Prasad et al, 2018;Ji et al, 2019). While complement activation has been previously demonstrated in the brain during Toxoplasma infection, the common functions of C4A point toward a possible role in increasing vascular permeability gradually during chronic infection for the continued infiltration of peripheral immune cells into the brain (Xiao et al, 2016;Huang et al, 2019). Interestingly, BALB/c mice experience significantly less expression of C4A at each infection time point compared to C57BL/ 6 mice which is an indication that there is decreased vascular permeability in these mice compared to B6.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C4A has been associated with roles in schizophrenia (Liesmaa et al, 2018;Melbourne et al, 2018;Prasad et al, 2018;Ji et al, 2019). While complement activation has been previously demonstrated in the brain during Toxoplasma infection, the common functions of C4A point toward a possible role in increasing vascular permeability gradually during chronic infection for the continued infiltration of peripheral immune cells into the brain (Xiao et al, 2016;Huang et al, 2019). Interestingly, BALB/c mice experience significantly less expression of C4A at each infection time point compared to C57BL/ 6 mice which is an indication that there is decreased vascular permeability in these mice compared to B6.…”
Section: Discussionmentioning
confidence: 99%
“…These changes were associated with neurodegeneration ( Li et al, 2019 ). An avirulent Toxoplasma strain also caused upregulation of complement proteins, including C3, C4b, and C1q, in the mouse brain ( Huang et al, 2019 ). Furthermore, mRNAs for FB and FP, C3aR, and C5aR were up-regulated in the brain of mice chronically infected with an avirulent Toxoplasma strain ( Shinjyo et al, 2021 ), suggesting that the alternative pathway is activated in the brain during chronic infection.…”
Section: Interactions Between Infectious Agents and Complement In The Cnsmentioning
confidence: 99%
“…In Toxoplasma-infected brain, complement components (C3, C4b, and C1q) were upregulated possibly causing the disruption of tight junctions. Huang et al, 2019 3 (in vivo) Persistent infection model: Type I T. gondii (GT1) in mice (5 months post infection)…”
Section: Study Design Outcomes Conclusion Referencesmentioning
confidence: 99%
“…It has been proved that T. gondii can recruit C4BP and factor H from the host, inactivate the surface-bound C3 and limit C5b-9 from forming a membrane attack complex [ 17 , 18 ], eventually resulting in immune escape. It was reported that the complement pathway and tight junction (TJ) pathway have specific changes in mouse brain tissues because of the significant increase in C3 expression led by T. gondii infection [ 19 ]. C3 may be related to the process of T. gondii entering the host brain.…”
Section: Introductionmentioning
confidence: 99%